Health Literacy Among University Students: A Systematic Review of Cross-Sectional Studies - Kühn, Lucas; Bachert, Philip; Hildebrand, Claudia; Kunkel, Jule; Reitermayer, Jörg; Wäsche, Hagen; Woll, Alexander (Frontiers in Public Health, 2022)
Objective: The aim of this systematic review is to provide an overview of cross-sectional studies that examined health literacy among university students and to identify possible determinants related to health literacy. Method: The current review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta Analyses. Three databases (PubMed, Scopus, and Web of Science) were systematically searched for cross-sectional studies that examined health literacy among university students. Results of included studies were narratively summarized. Results: The systematic review includes twenty-one research studies. The majority of studies report health literacy scores among university students that are lower compared to reference samples. Health literacy of students is influenced by different variables (age, gender, number of semesters, course of studies/curriculum, parental education, and socioeconomic background). Discussion: Health literacy activities should target all students. Universities should make use of their resources and offer health literacy courses for students in which content is used from disciplines available at the university (e.g., medicine, health, or psychology). To increase effectiveness, health literacy courses should be adapted according to the different needs and characteristics of the student subgroups.